Penerapan Maharoh Kitabah dalam Pembelajaran Bahasa Arab Melalui Metode Diskusi dan Latihan di SMP Islam Mathooli’ul Anwar Lampung Tengah - Rosidah, Mughiatur; Nur, Kholida; Faedurrohman (CV. Creative Tugu Pena, 2024)
This research is an assessment that occurs in class. Writing skills are still lacking due to the difficulty of putting together sentences that are appropriate to this learning method. The aim of this research is to evaluate students' abilities during learning, so that educators can know more. This study uses qualitative research, namely data collection by face-to-face and interacting with people at the research site. While the type of research used is descriptive qualitative field research. the subjects in this research are 7th grade students of Mathooli'ul Anwar Islamic Middle School with a total of 3 students and 8 female students for the 2023/2024 academic year. This research data was obtained from observation, interviews and tests. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The research results show that using this discussion and practice method can improve students' sentence writing abilities. The students also responded positively to the use of discussion and practice methods. Teachers can apply discussion and practice methods as an alternative to improve the ability to write sentences and for educational institutions to better prepare facilities and infrastructure for learning so that it can run optimally. Future researchers can use the same method with different goals of improving Arabic language skills.